Effect of heat load on microstructural development in an irradiated low alloy steel. (August 2018) - Goto, Shunta; Hashimoto, N.
Abstract: To investigate the influence of heat load on microstructure change, we conducted in-situ experiments of annealing and irradiation for a model alloy (Fe-0.75Mn-0.47Mo-0.45Ni) using a multi-beam high voltage electron microscope. Electron-irradiation resulted in the formation of black dots in the model alloy. It is noted that some of black dots grew and changed to dislocation loops, but some did not. Furthermore, the 500 °C annealing to the electron-irradiated sample resulted in the shrinkage and/or the disappearance of black dots and small loops (<10 nm). It is suggested that the annealing would cause the release of interstitial atoms from small loops, which could flow into adjacent larger loops or diffuse to the surface.